2018
DOI: 10.1111/eos.12571
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid attenuates inflammation‐induced hyperexcitability of trigeminal spinal nucleus caudalis neurons associated with hyperalgesia in rats

Abstract: The present study investigated whether daily systemic administration of docosahexaenoic acid (DHA) in rats could attenuate the hyperexcitability of trigeminal spinal nucleus caudalis (SpVc) neurons associated with hyperalgesia. Inflammation was induced in rats by injecting complete Freund's adjuvant into the whisker pads. The threshold of escape from mechanical stimulation applied to the whisker pads in inflamed rats was significantly lower than that in naïve rats. The lowered mechanical threshold in the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…10 We first confirmed that CFA induced hyperexcitability of SpVc WDR neurons, as described in our previous studies. [10][11][12][13] In naïve rats, spontaneous discharges were observed in 17% (1/6) of SpVc neurons (Figure 3(a) and Figure 4(c)) while most neurons fired at a low frequency with a mean firing frequency of 0.1 ± 0.2 Hz (n = 6). In contrast, all WDR neurons (6/6; 1.9 ± 0.6 Hz) were spontaneously active in inflamed rats (Figure 3(b) and Figure 4(c)).…”
Section: Changes In Excitability Of Spvc Wdr Neurons Following Inflam...mentioning
confidence: 99%
“…10 We first confirmed that CFA induced hyperexcitability of SpVc WDR neurons, as described in our previous studies. [10][11][12][13] In naïve rats, spontaneous discharges were observed in 17% (1/6) of SpVc neurons (Figure 3(a) and Figure 4(c)) while most neurons fired at a low frequency with a mean firing frequency of 0.1 ± 0.2 Hz (n = 6). In contrast, all WDR neurons (6/6; 1.9 ± 0.6 Hz) were spontaneously active in inflamed rats (Figure 3(b) and Figure 4(c)).…”
Section: Changes In Excitability Of Spvc Wdr Neurons Following Inflam...mentioning
confidence: 99%
“…The present authors recently tested the hypothesis that intraperitoneally administered dietary constituents could attenuate SpVc neuronal hypersensitivity related to mechanical hyperalgesia induced by complete Freund's adjuvant (CFA) [62,63]. In addition, the authors showed that resveratrol, DHA, and lutein provided in the diet inhibited inflammatory mechanical hyperalgesia and associated nociceptive neuronal hyperexcitability induced by CFA, possibly by inhibiting the Cox-2 converting enzyme from arachidonic acid to PGE 2 [64][65][66]. This experimental series showed (i) that the lowered escape threshold for mechanical stimulation in inflamed rats returned to control levels with ongoing administration of dietary constituents, (ii) that dietary components also reversed the high-frequency SpVc WDR discharges elicited by mechanical non-noxious and noxious stimuli, (iii) that dietary constituents returned the spontaneous discharges rates of SpVc WDR neurons as well as the noxious pinch-evoked after-discharge frequency in inflamed rats, and (iv) that control levels of receptive field expansion in inflamed rats were attained [64][65][66].…”
Section: How Do Dietary Constituents Mechanistically Modulate Inflammmentioning
confidence: 97%
“…In addition, the authors showed that resveratrol, DHA, and lutein provided in the diet inhibited inflammatory mechanical hyperalgesia and associated nociceptive neuronal hyperexcitability induced by CFA, possibly by inhibiting the Cox-2 converting enzyme from arachidonic acid to PGE 2 [64][65][66]. This experimental series showed (i) that the lowered escape threshold for mechanical stimulation in inflamed rats returned to control levels with ongoing administration of dietary constituents, (ii) that dietary components also reversed the high-frequency SpVc WDR discharges elicited by mechanical non-noxious and noxious stimuli, (iii) that dietary constituents returned the spontaneous discharges rates of SpVc WDR neurons as well as the noxious pinch-evoked after-discharge frequency in inflamed rats, and (iv) that control levels of receptive field expansion in inflamed rats were attained [64][65][66]. Taken together, these findings indicate that resveratrol, lutein, and DHA significantly limited mechanical hyperalgesia induced by inflammation, probably by primary suppression of SpVc WDR neuronal hyperexcitability after attenuated peripheral COX-2 signaling (Fig.…”
Section: How Do Dietary Constituents Mechanistically Modulate Inflammmentioning
confidence: 99%
See 2 more Smart Citations